Боротьба комуністичної влади з дисидентами в Україні (1987–1989 рр.) - Demianczuk, Witalija (Komunizm: System - Ludzie - Dokumentacja, 2015)
The article analyzes the socio-political activity of Ukrainian dissidents in 1987-1989 and the struggle against them led by the Communist Party of Ukraine. Presents the anti-Soviet nature of their activities in the eyes of authority. In particular, the article shows their political actions which had a broad social resonance.